2010
DOI: 10.1108/07378831011047695
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting the archives perspective in the personal digital archiving discussion

Abstract: PurposeThe topic of personal archives has mainly been discussed by two research traditions in information science: archives and records management, and personal information management. The purpose of this paper is to compare a corpus of the archival literature written by the archival community with the concepts and challenges posed by Catherine Marshall, who exemplifies the personal information management approach. Many of the personal digital archiving challenges that Marshall identifies are related to discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Other authors (Bruce, Jones and Dumais 2004, Williams, Leighton John and Rowland 2009, Huvila, Eriksen, Häusner and Jansson 2014 have also discussed these issues and concluded that individuals exhibit different levels of awareness, employ different keeping methods and different archiving and preservation strategies and practices while appreciating the ability to use information in the future and to benefit from its pluralisation. Personal information management has also been considered and discussed in the context of archival practices and personal digital archiving (Cushing 2010). And while Cushing discussed conceptual positioning of the topic, Bergman (2010) emphasized methodological issues by identifying 15 variables that characterize different personal information management behaviours.…”
Section: Digital Curationmentioning
confidence: 99%
See 4 more Smart Citations
“…Other authors (Bruce, Jones and Dumais 2004, Williams, Leighton John and Rowland 2009, Huvila, Eriksen, Häusner and Jansson 2014 have also discussed these issues and concluded that individuals exhibit different levels of awareness, employ different keeping methods and different archiving and preservation strategies and practices while appreciating the ability to use information in the future and to benefit from its pluralisation. Personal information management has also been considered and discussed in the context of archival practices and personal digital archiving (Cushing 2010). And while Cushing discussed conceptual positioning of the topic, Bergman (2010) emphasized methodological issues by identifying 15 variables that characterize different personal information management behaviours.…”
Section: Digital Curationmentioning
confidence: 99%
“…Thus we can conclude that there is and will be a great need for vocational education and training for digital curators who will use their skills for long-term preservation and management of digital data and content in information institutions and cultural and heritage institutions. As literature suggests and some studies indicate (Cushing 2010, Fourie 2011, Marčetić 2014, the general population, as well as members of academia, often need or rely upon the help from information professionals when it comes to organizing, preserving and curating their digital assets and memories for life; and will do so in the future, especially in the context of creating great amount of data on a daily basis. When one thinks of concepts that are already here, such as big data, cloud computing and smart systems, and of those that are coming in the future, such as hyper-reality technologies and quantum computing, anticipation and careful planning have become just as important as raising awareness.…”
Section: Digital Legacymentioning
confidence: 99%
See 3 more Smart Citations